2022
DOI: 10.3390/rs14092018
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Tsunami Potential Assessment Using GNSS Ionospheric Disturbance: Implications from Three Megathrusts

Abstract: The current tsunami early warning systems always issue alarms once large undersea earthquakes are detected, inevitably resulting in false warnings since there are no deterministic scaling relations between earthquake size and tsunami potential. In this paper, we assess tsunami potential by analyzing co-seismic ionospheric disturbances (CIDs). We examined CIDs of three megathrusts (the 2014 Mw 8.2 Iquique, the 2015 Mw 8.3 Illapel, and the recent 2021 Mw 8.2 Alaska events) as detected by Global Navigation Satell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Li et al studied the propagation direction of the Alaska earthquake ionosphere anomaly and found that the Alaska earthquake anomaly was mainly concentrated in the direction of east-northeast of the epicentre, and the vertical crustal displacement caused by the earthquake rupture was not significant 28 . In order to further detect the ionosphere anomaly of Alaska earthquake, the specific propagation direction of the Alaska earthquake, we apply a new method to study the anomalous propagation direction of the Alaska earthquake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al studied the propagation direction of the Alaska earthquake ionosphere anomaly and found that the Alaska earthquake anomaly was mainly concentrated in the direction of east-northeast of the epicentre, and the vertical crustal displacement caused by the earthquake rupture was not significant 28 . In order to further detect the ionosphere anomaly of Alaska earthquake, the specific propagation direction of the Alaska earthquake, we apply a new method to study the anomalous propagation direction of the Alaska earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…Although GNSS technology has been used to study the Mw8.2 Alaska earthquake, there have been few previous studies on the azimuth of large anomalies in the earthquake, and no specific research on the propagation direction of CIDs 28 . Therefore, based on the study of the disturbance sources and the spatio-temporal variation characteristics of the Alaska earthquake, this paper further quantitatively studies the specific direction of the anomaly propagation of the Alaska earthquake, which provides a certain reference value for the later study of the propagation direction and mechanism of the CIDs of the same earthquake in the high-incidence area, and for the earthquake monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies by Thomas et al (2018) [22], Astafyeva and Shults (2019) [23], and Sanchez et al (2023) [24] reported the detection of ionoquakes at altitudes of 150-190 km, in which results are below the maximum ionization altitude of the surrounding ionosphere. Moreover, a substantial number of research findings consistently illustrate that the initial SAI coupling in proximity to the earthquake epicenter typically manifests within a timeframe of 8 min following the initiation of the seismic event [1,2,[7][8][9][10][11][12][13]25].…”
Section: Introductionmentioning
confidence: 93%
“…Numerous studies report the detection of coseismic ionospheric disturbances or ionoquakes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Their origin involves seismo-atmosphere-ionosphere (SAI) coupling, acoustic gravity waves (AGWs) [16][17][18] and co-seismic thermospheric disturbance (CSTD) energetics [19][20][21].…”
Section: Introductionmentioning
confidence: 99%